The Age of Deer : Trouble and Kinship with our Wild Neighbors - Howsare, Erika (New York : Catapult, 2024)
In this masterful hybrid of nature writing and cultural studies, the author investigates our connection with deer, from mythology to biology, offering a unique and intimate perfective on a very human relationship while inviting us to contemplate the paradoxes of how we interact with and shape the natural world.
Introduction -- Part 1: Standing. Dancing -- Goods -- The graph -- Value -- Kinfolk -- Part II: Struggling. Capacity -- Decline -- Management -- Should not be -- Bodies -- Pests -- The cull -- Victims -- Part III: Craving. The fetish -- For show -- November dawns -- Craving.
Includes bibliographical references (pages 305-336).
Keywords: Deer; Deer -- Effect of human beings on; Human-animal relationships; Animal welfare; Animals and civilization